2019
DOI: 10.1002/adma.201902900
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial‐Infarction‐Responsive Smart Hydrogels Targeting Matrix Metalloproteinase for On‐Demand Growth Factor Delivery

Abstract: Although in situ restoration of blood supply to the infarction region and attenuating pre‐existing extracellular matrix degradation remain potential therapeutic approaches for myocardial infarction (MI), local delivery of therapeutics has been limited by low accumulation (inefficacy) and unnecessary diffusion (toxicity). Here, a dual functional MI‐responsive hydrogel is fabricated for on‐demand drug delivery to promote angiogenesis and inhibit cardiac remodeling by targeting upregulated matrix metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 50 publications
1
135
0
Order By: Relevance
“…It was shown that an MMP‐responsive hydrogel alleviated MI‐induced vascular wall thinning and promoted the proliferation of vascular cells. [ 130 ] It is quite convenient to link hydrogels with protease cleavable linkers for responsive delivery. Similar MMP‐responsive features were adopted in SDF‐1α delivery.…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that an MMP‐responsive hydrogel alleviated MI‐induced vascular wall thinning and promoted the proliferation of vascular cells. [ 130 ] It is quite convenient to link hydrogels with protease cleavable linkers for responsive delivery. Similar MMP‐responsive features were adopted in SDF‐1α delivery.…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
“…MMP‐2/9 cleavable hydrogel that achieved on‐demand bFGF release for myocardial infarction. [ 130 ] A) Schematic illustration of the preparation and the process of the responsive release from the MMP responsive injectable hydrogel. B) bFGF release triggered by MMP‐2 at different time points.…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
“…et al, 2019;Zhu et al, 2019). Meanwhile, hydrogel-based drug delivery systems for numerous therapeutic agents, with high water content, low interfacial tension with biological fluids, and soft consistency, have been shown to be more stable, economical, and efficient in comparison with conventional delivery systems (Li and Mooney, 2016;Moore and Hartgerink, 2017;Cheng et al, 2019;Fan et al, 2019;Zheng et al, 2019). Considering the above advantages, hydrogels have been conducted into the biomedical application to provide a tunable three-dimensional scaffold for cell adhesion, migration, and/or differentiation, and they could also be designed as the platform for the controlled release of cytokines and drugs in tissue engineering and drug delivery (Huang et al, 2017;Jiang et al, 2017;Hsu et al, 2019;Wei et al, 2019;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, favorable cell delivery via injectable hydrogel system can be a stimulating and effective alternative to attain the targeted site delivery of huge numbered live cells. Many biodegradable hydrogels designed containing a broad range of favorable mechanical and biocompatible properties have been investigated by clinical animal models to regeneration of myocardial infarction, cardiovascular diseases, etc., Numerous reported studies were suggested that high modulus injectable hydrogel matrix with conductive properties could be greatly in uence on recovery of heart functions after myocardial infarction [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%